2015
DOI: 10.1021/acs.chemmater.5b02357
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in Co-Alloyed Titanium Oxynitrides, a Promising Class of Photochemically Active Materials

Abstract: We present a perspective on recent developments in modified TiO 2 photocatalysts for visible light-driven photochemistry with an emphasis on water splitting. We focus on doped and alloyed TiO 2 and in particular address the synergistic effects observed in materials with both transition metal cations and nonmetal anions. Several reports have demonstrated absorption of longer wavelengths (λ = 500−600 nm) by codoped materials compared to the absorption edge of TiO 2 . We review these advances against the backdrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 115 publications
0
27
0
Order By: Relevance
“…Deposition of metal particles to improve the performances of titania thin films by heterojunction, co-catalysis, co-alloying or plasmonic effects has been widely investigated [16][17][18][19], with recent studies remarking also the role of one-dimensional nanoarchitecture (e.g. nanotubes) [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Deposition of metal particles to improve the performances of titania thin films by heterojunction, co-catalysis, co-alloying or plasmonic effects has been widely investigated [16][17][18][19], with recent studies remarking also the role of one-dimensional nanoarchitecture (e.g. nanotubes) [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the different behaviour of metals and non‐metals, co‐doping was used as a strategy to enhance the photocatalytic activity of TiO 2 , . It is reported that anions and cations generate shallow localized levels near the valence and conduction band edges, allowing the band gap decrease and the shift of the two bands towards less positive and less negative values, respectively . Various N, W co‐doped TiO 2 systems have been prepared and tested under solar light irradiation for oxidation reactions .…”
Section: Introductionmentioning
confidence: 99%
“…While some PCO-based technologies have been evaluated [1019], research addressing the development and evaluation of visible light driven PCO materials is limited [2023]. It is known, however, that materials such as TiO 2 can be co-alloyed with niobium (Nb) and oxynitrites to significantly reduce adsorption energy down to 2.0 eV, which enables visible light activation [2426]. Most evaluations have focused on NO x (NO, NO 2 ) removal using UV lights for outdoor applications [2732].…”
Section: Introductionmentioning
confidence: 99%